2007
DOI: 10.1155/2007/80687
|View full text |Cite
|
Sign up to set email alerts
|

Thermolabile Methylenetetrahydrofolate Reductase C677T Polymorphism and Homocysteine Are Risk Factors for Coronary Artery Disease in Moroccan Population

Abstract: Increased plasma total homocysteine (tHcy) levels have been shown to be a risk factor for coronary artery disease (CAD). The common methylenetetrahydrofolate reductase C677T (MTHFR C677T) polymorphism has been reported to be a strong predictor of mild hyperhomocysteinaemia (HHcy). We assessed whether this mutation was associated with increased risk of CAD and plasma levels of tHcy. We also evaluated interactions between this polymorphism, mild elevated tHcy levels and conventional risk factors of CAD. Method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
(43 reference statements)
5
16
1
3
Order By: Relevance
“…Previous studies have reported Hcy concentrations ranging from 6 µmol/L in Japan to 13 µmol/L in South Africa in healthy subjects [4]. In the Iranian population, Hcy concentrations were lower [7. µmol/L] [7]. The similar levels of Hcy in Syria and Morocco compared with our findings may be due to similarities in food intake habits.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have reported Hcy concentrations ranging from 6 µmol/L in Japan to 13 µmol/L in South Africa in healthy subjects [4]. In the Iranian population, Hcy concentrations were lower [7. µmol/L] [7]. The similar levels of Hcy in Syria and Morocco compared with our findings may be due to similarities in food intake habits.…”
Section: Discussionsupporting
confidence: 79%
“…Genes encoding proteins that perform or support these conversions include MTHFD1, MTHFR, MTR, and MTRR. MTHFR polymorphisms are widely studied in coronary artery disease, neural tube defects, and facial clefts [selected recent publications: Bennouar et al, 2007;Chevrier et al, 2007;Munoz et al, 2007]. The folate cycle is coupled to one-carbon metabolism by the MTR-mediated conversion of homocysteine to methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Em DAC, o alelo polimórfico foi observado significantemente mais freqüente nos pacientes em relação aos controles [10][11][12][13][14]25 . Em estudo brasileiro, o polimorfismo foi associado à gravidade da doença, mas não apresentou distribuição significantemente diferente entre pacientes com e sem DAC 26 .…”
Section: Discussionunclassified